Equilibrium Exchange Rates in Transition Economies - Halpern, Lionel (IMF Working Papers; Working Paper ;, 1996)
A stylized fact of the transition process is an early profound exchange rate depreciation followed by continuing real appreciation. Absent historical reference points, it is difficult to judge whether the real appreciation is threatening competitiveness. This paper interprets the stylized facts and offers estimates of the equilibrium real exchange rate based on an international comparison of dollar wages and on a study of the dynamics of real exchange rates in several transition economies. The results suggest that the process of real appreciation is a combination of a return to equilibrium following the early overshooting and equilibrium appreciation.